Guia prático de utilização de terapêuticas biotecnológicas na artrite reumatóide-actualização de dezembro 2011 - Mourão, Ana Filipa (2011)
The authors review the practical aspects of biologi -cal therapy use for rheumatoid arthritis patients, commenting safety issues before and after treatment initiation and the best treatment strategies to optimize efficacy.